A congenital intraspinal gastroenterogenous cyst in diastematomyelia. Issue 6 (December 1973) - Bale, Patricia M.
Abstract : A female neonate, with neurological signs and leucocytosis in sterile spinal fluid, was found to have anomalies of the upper thoracic vertebral bodies with a bony spur indicating diastematomyelia. The spur was removed, but symptoms recurred. Necropsy at the age of 5 months revealed an intraspinal gastroenterogenous cyst containing a perforated peptic ulcer. Analysis of eight previous reports of intraspinal enterogenous cysts, shows that, like prevertebral enterogenous cysts, they are frequently combined with defects in the vertebral bodies. This association suggests development from an embryonic ectoendodermal adhesion. Vertebral body defects are a significant pointer to the diagnosis and should not be overlooked, as curative resection is sometimes possible.